(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Traumatic rupture of the diaphragm is rarely observed in children with thoracoabdominal trauma. Although dyspnea is the commonest symptom, early diagnosis is difficult as chest radiography can diagnose only half of the cases. Prompt diagnosis and surgical repair is life saving. Patient may suffer from multiple associated injuries which is often fatal. A 8 years old boy was admitted with severe respiratory distress and restlessness follwing a history of landslide few hours back. He was pale, cyanosed with hypotension, tachycardia and sweating. Bruise noted over left upper abdomen and left lower chest wall. Surgical emphysema and restricted movement during respiration was noted in the left chest wall with absent breath sound. Abdomen was scaphoid having normal bowel sound. Resuscitation was started and insertion of left intercostal chest drain tube had failed to relieve respiratory distress. A portable chest radiograph showed the chest drain tube in abdomen with mediastinal shifting to opposite side and collapsed lung margin. Left dome of the diaphragm was not clearly visualized. Re institution of chest tube was planned for immediate relief and on withdrawal of the previous drain tube dragged the omentum with it. Then the diagnosis of diaphragmatic rupture was obvious. Laparotomy showed extensive tear of left hemidiaphragm with herniation of abdominal contents. Left costal margin was also torn but abdominal viscera were found intact. Repair was done with interrupted unabsorbable suture after keeping a chest drain tube. Post operatively the patient was kept in ward with adequate analgesia. Check X-ray on 1st post operative day, showed well expanded left lung. The patient had recovered well. Drain was removed on 3rd postoperative day and was discharged on 7th post operative day. High index of suspicion is needed for correct diagnosis. Outcome is satisfactory if treated in time without any associated injury. J. Paediatr. Surg. Bangladesh 3(2): 81-84, 2012 (July)